Changing Approaches to Development since 1950: Drawing on Polanyi - Stewart, Frances (History of Political Economy, 2018)
The article focuses on analysis of Karl Polanyi in the book "The Great Transformation" which explained the changes in Great Britain from eighteenth-century mercantilism to nineteenth-century free markets to the state-centered interventionism of the mid-twentieth century evident when he was writing. It mentions additional features needed for understanding the evolution of development thought and repeal of the Corn Laws in 1846, leading to free trade in agricultural products.
Keywords: Great Transformation, The (Book); POLANYI, Karl, 1886-1964; economic development; free enterprise; free trade; mercantile system

Tensions in the Triangle: Monetary Plurality between Institutional Integration, Competition and Complementarity - Blanc, Jerome (Evolutionary and Institutional Economics Review, 2018)
This text aims at accounting for the plurality of money by emphasizing the delicate and evolving balance of the legal monetary systems and the continued existence of moneys that stay outside, though their continuation is subjected to chronic difficulties. It uses Polanyian concepts to take the wide and increasing variety of money into account and mobilizes criteria able to analyse the variety of links between them. It proposes a framework based on the representation of a "plurality triangle" with institutional integration, complementarity and competition, and it analyses the positioning of moneys in this framework as well as tensions that may generate shifts in their positioning.
Keywords: current heterodox approaches: historical; evolutionary; institutional; monetary systems; money

Terrains of Civil and Uncivil Society in Post-Apartheid Durban - Bond, Patrick; Mottiar, Shauna (Urban Forum, 2018)
Post-apartheid Durban civil society politics reflects not only durable anti-racist activism, but primarily, Karl Polanyi's pendulum of a 'double movement' of the market against people and environment on the one hand, and social backlashes against neoliberalism on the other. The most important movements and campaigns of a socioeconomic nature can be summarised as follows: local resistance to economic disempowerment and lack of service delivery in various trade union strikes (1994-present), South Durban's fight against polluters and the port's expansion (1996-present), Chatsworth's water and electricity battles (1999-2012), the Treatment Action Campaign's access to AIDS medicines (early 2000s), Abahlali baseMjondolo's anti-eviction campaigns (2005-present), the defence of the Early Morning Market (2009-10), the Umlazi Occupy (2012), and sporadic community protests throughout. Resistance has occurred in urban poor neighbourhoods and townships and also penetrated the Durban inner city and university campuses. Durban activists' tactics range from militant protests to 'occupation' of space ranging from townships to the Speaker's Corner next to the Convention Centre, innovative door-to-door campaigning and court action. While the limits of single-issue and often assimilationist civil society politics are becoming obvious in one of the world's most unequal cities, there still has not yet been a successful 'united front' project to fuse interests, in part due to ideological division and the geographical diffusion of dissent.
Keywords: Durban; HIV/AIDS; South Africa; Treatment Action Campaign; anti-racism; apartheid; civil society; demonstrations (collective behavior); double movement; environmental justice; protest; social movements; socioeconomics; trade unions

Polanyi, Hayek and embedded neoliberalism - Cahill, Damien (Globalizations, 2018)
Written originally on the seventieth anniversary of the publication of Friedrich von Hayek’s The Road to Serfdom and Karl Polanyi’s The Great Transformation, this article critically analyses how the ideas of Hayek and Polanyi have been deployed to understand neoliberalism. It argues that dominant scholarly interpretations tend to miss the significance of each thinker to an understanding of neoliberalism, as well as some of the key dynamics of neoliberal forms of capitalist regulation. Drawing upon the work of Polanyi, the article advances the concept of embedded neoliberalism. From the 1970s neoliberal regulations became deeply embedded in a series of institutions, class relations and ideological norms. This helps to explain both the durability of neoliberalism, and the onset of crisis in 2008. In this context, Hayek’s ideas are best understood as providing a malleable set of concepts underpinning neoliberal ideology, rather than the chief causal agent in the neoliberal transformation of states and economies.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; capitalism; embeddedness; liberalism; neoliberalism

Between perfection and damnation: The emerging geography of markets - Cohen, Dan (Progress in Human Geography, 2018)
Economic geographers have recently taken up the study of markets after a long period of inattention. This growing literature has highlighted the diverse spaces, scales, and fields where markets are present, as well as the ways in which markets vary in form. However, the study of markets in economic geography still exists in tension between neoclassical and Marxist conceptions of markets as predictable and approaches like the social studies of economization/marketization which emphasize their contingency. This paper argues that work of Polyani and Gramsci can provide a way forward for the subfield through conceptualizing markets as sites of social struggle.
Keywords: capitalism; counterhegemony; earth scientists; economic geography; economic systems; geographers; human geography; marketization; markets; neoliberalism

‘Our world was made by nature’: constructions of spontaneous order - Dale, Gareth (Globalizations, 2018)
This article explores the concepts of spontaneity and spontaneous order, in particular their deployment by Friedrich Hayek and Karl Polanyi. Although in many respects these thinkers were poles apart, the article identifies a point of convergence. They both mobilize the concept of spontaneity in a manner that naturalizes a particular social process: for Hayek, the market economy, for Polanyi, society’s protective movement that arises in reaction against the market economy. To contextualize the uses of spontaneity by Hayek and Polanyi, I trace its evolution, with reference to Leibniz, Mandeville, and the thinkers of the Scottish Enlightenment. Having sketched the ways in which earlier thinkers understood spontaneity, I turn finally to Hayek and Polanyi. I argue that their invocations of spontaneity and spontaneous order contribute to a downplaying of relations of domination and exploitation. While Hayek sees the market system as the exemplar of spontaneous order, for Polanyi, the concept of spontaneity underpins his belief that the protective countermovement is a ‘natural’ reaction to the evils of market society; as such, power relations pass beneath the radar.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; HAYEK, Salma, 1968-; POLANYI, Michael, 1891-1976; social order; socialism; spontaneity; spontaneity (philosophy); spontaneous order

Democracy disembedded - Dimitrijevic, Nenad (Philosophy & Social Criticism, 2018)
Democracy is in serious difficulties. Three features of the crisis stand out. First is the dominant culture of disillusionment in democracy, which transpires as the mistrust in constitutionalist institutions and values. Second, political authority, both at domestic and international levels, is largely substituted by the rule of non-transparent and unpredictable social powers. Third, democratic states are deprived of much of their capacity to govern, but they retain a non-negligible capacity to coerce.The article is structured as follows. Section I introduces Karl Polanyi’s concept of embeddedness and juxtaposes it to the theoretical defense of market disembeddedness advanced by the classical political economy. It then points to the challenge that the complexity of the contemporary society poses to the idea of embeddedness and identifies the need for further analytical clarification of the idea. Section II tries to explain why the idea of embeddedness is intuitively suspect. One reason is found in the dominant understanding of liberalism as a regime that rests on the separation between private and public realms. The section closes with a reference to internal tensions of this reading of liberalism. Section III provides a diagnosis of the contemporary condition of disembeddedness. The core claim is that the combination of neoliberalism and globalization has created a condition of multiple—normative, social, political and legal—disintegration, which questions the very survival of democracy. Section IV addresses the question of transformation, focusing on the need for the reconceptualization of liberal equality.
Keywords: POLANYI, Karl, 1886-1964; democracy; disembeddedness; embeddedness (socioeconomic theory); equality; globalization; liberalism

Polanyi’s two transformations revisited: a ‘bottom up’ perspective - Halperin, Sandra (Globalizations, 2018)
In The Great Transformation, Karl Polanyi offers a ‘top-down’ analysis of the rise and demise of Europe’s unregulated market system. He assumes that changes in the organization of the international economy provide particular kinds of opportunities for states to act which, in turn, shapes the extent to which social forces will be able to influence state policy. Consequently, his analysis focuses, first, on the international institutions created by the self-regulating market system; then on the ‘liberal state’ which these made possible; and finally on how the system impacts ‘society as a whole’. The account which this analysis produces systematically underplays the social struggles which propelled and emerged from the rise of Europe’s nineteenth century system and which ultimately led to its demise. In revisiting the two periods that are the focus of Polanyi’s analysis, this article assumes that states and interstate systems reflect the interests of powerful social forces. Thus, working from the ‘bottom up’, it focuses on the class interests that produced Europe’s market system, the state and international structures which reflected and supported them, and the social struggles that ultimately brought about the collapse of the system. What this ‘bottom up’ account reveals is the centrality of a ‘double movement’, not of market expansion and a protective countermove on the part of ‘society as a whole’, but of dominant classes monopolizing economic opportunities from global expansion, and a rising ‘red tide’ of disaffected workers. This double movement, it argues, better explains the demise of the system and the changes that ensued from it.
Keywords: class conflict; double movement; economic development; industrial capitalism; international relations; markets

Against exceptionalism: the legitimacy of the neoliberal age - Konings, Martijn (Globalizations, 2018)
After the financial crisis of 2007-08, many commentators, adopting a broadly Polanyian logic of reasoning, expected a departure from neoliberalism. The failure of this shift to materialize has typically been accounted for in ‘exceptionalist’ terms: the persistence of neoliberalism is understood not as a function of a specific legitimacy it has itself engendered, but in terms of external interventions by elites who manage to ‘capture’ executive and regulatory institutions and so to bypass democratic pressures. This paper argues that such an approach underestimates the endogenous sources of legitimacy and resilience that neoliberal governance commands. It criticizes the idea that neoliberalism is at its core dependent on a Schmittian exceptionalism and suggests a perspective on Hayek's articulation of neoliberalism that dissociates it from such an exceptionalist approach. The article proceeds to interrogate the rationality of neoliberalism by examining its distinctively secular temporal logic, rooted in speculation, preemption and reaction.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; capitalism; exceptionalism; legitimacy; neoliberalism; preemption

Polanyi vs Hayek? - Mirowski, Philip (Globalizations, 2018)
Karl Polanyi and Friedrich Hayek are often portrayed as implacable intellectual opponents but their respective historical trajectories suggest some telling similarities. Here we describe some key similarities in their approach to markets, as a prelude to evaluating the political consequences of relying upon their Austrian conceptions of nature-based and constructivist framing of markets. Perhaps it is time to transcend their dichotomy.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; POLANYI, Karl, 1886-1964; POLANYI, Michael, 1891-1976; constructivism; markets; science and technology; spontaneous order

The great trasformismo - Morton, Adam David (Globalizations, 2018)
The purpose of this article is to explore the commonalities and differences between Karl Polanyi and Antonio Gramsci in their assessment of the origins of fascism as located within the rise of capitalism in the nineteenth century and its structural impasse in the twentieth century. Specifically, the aim is to trace a set of associations between Polanyi and Gramsci on the transformations wrought across the states-system of Europe prior to the crises that engulfed capitalism leading to the rise of fascism in the twentieth century. Focusing on the class structures that emerged out of the expansion of capitalism across Europe in the nineteenth century reveals that there was less a ‘great transformation’ in terms of a rupture with the past through the rise of liberal capitalism. Rather, there was more a slow and protracted process of class restoration known as passive revolution, or a ‘Great Trasformismo’, referring to the molecular absorption of class contradictions marking the consolidation and expansion of capitalist social relations. In sum, it is argued that The Great Transformation is understood better if read through the epoch of passive revolution, or The Great Trasformismo, which entailed the restoration and maintenance of class dominance through state power. This approach therefore opens up questions, rather than forecloses answers, about the historical geographies constituting the spaces and places of the political economy of modern capitalism.
Keywords: GRAMSCI, Antonio, 1891-1937; POLANYI, Karl, 1886-1964; capitalism; fascism; passive revolution

Karl Polanyi as a spatial theorist - Roberts, Philip (Globalizations, 2018)
The ‘spatial’ turn in political economy has re-invigorated Marxian analysis, allowing for new research programmes into urbanization, geopolitics, and social movement activity amongst other topics. This tendency emerged through a critical re-reading of Marx and Gramsci, amongst others, uncovering spatial analyses embedded in the logic of their arguments. Conversely, Karl Polanyi’s interlocutors have tended to add geographical analysis as an additional layer of theory, reading space ‘in’ to the text. However, a close reading reveals that a concern with space permeates Polanyi’s analysis. As such, it is possible to read space ‘out’ of Polanyi, adding a level of theoretical rigour and logical consistency when applying his insights to geographic topics. This article carries out an exegesis of Karl Polanyi’s work, uncovering a theoretical framework that deals with space, place, scale, fixity, and motion. From this vantage point, the article considers the potential implications of this new geographical reading of Polanyi.
Keywords: Marxist philosophy; POLANYI, Karl, 1886-1964; capitalism; geography; international political economy; neoliberalism; scale; social sciences; space; spatial turn

Neoliberalism as a real utopia? Karl Polanyi and the theoretical practice of F. A. Hayek - Rodrigues, João (Globalizations, 2018)
This article interprets Hayek’s theoretical practice with the help of Polanyi’s framework. Hayek aimed at renewing liberalism after the interwar period, thus helping transforming it into neoliberalism, a real utopia instrumentally concerned with the political and moral economies underpinning markets. The distance between neoliberal theory and practice is less pronounced than it is sometimes assumed. The strength of neoliberalism partially stems from a capacity to articulate an effort to think about real-world mechanisms with an effort to demolish, reconfigure or transform existing structures. Despite his failure to anticipate neoliberalism, Polanyi gives ample intellectual resources to critically interpret the tasks that neoliberals would collectively have to face at the theoretical level, in an epoch of ideological marginality, before their triumphal political deployment at the global level.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; market; neoliberalism; utopia

Market/society: mapping conceptions of power, ideology and subjectivity in Polanyi, Hayek, Foucault, Lukács - Short, Nicola (Globalizations, 2018)
In light of discussions around the common anniversary of the publication of Karl Polanyi’s The Great Transformation and F.A. Hayek’s The Road to Serfdom, this article puts these texts - iconic representations of social democratic and neoliberal political theory - into conversation with Michel Foucault’s subsequent, influential critique of neoliberalism, The Birth of Biopolitics. There are interesting points of contact in the way each text constructs its argument, even as they arrive at distinct positions vis-à-vis the material and subjective nature of market society, while nevertheless sharing an opposition to Marxian approaches. Yet the work of Polanyi and Hayek’s Marxian contemporary, Lukács’ History and Class Consciousness, offers precisely a critical framework for understanding the relationship between markets, liberty and society in which the material and the subjective need not be read as antagonistic. It is thus also examined here, in an effort to shed light on how discussions of contemporary neoliberalism are framed.
Keywords: Canada; FOUCAULT, Michel, 1926-1984; HAYEK, Friedrich A. von (Friedrich August), 1899-1992; LUKACS, Georg; MARX, Karl, 1818-1883; Marxism; Road to Serfdom (book); commodity; homo economicus; market society; neoliberalism; power

Reading Polanyi in Erbil: understanding socio-political factors in the development of Iraqi Kurdistan - Smith, Robert (Globalizations, 2018)
The Kurdistan Regional Government emerges out of the chaos of post-Saddam Iraq as a rare positive, providing both political stability and economic growth. However, the outward display masks a more complex domestic settlement where the trappings of the free market coexist with political parties who are significant economic actors. How can this model of development in Iraqi Kurdistan be explained? Turning to the writings of political economist Karl Polanyi, does his thinking on relations between society and economy offer a way to unpack the development? And what does this analysis tell us of prospects for Iraqi Kurdistan?
Keywords: Iraq; Iraqi Kurdistan; Kurdistan; Kurdistan Regional Government; POLANYI, Karl, 1886-1964; international studies

Correlated ownership: Polanyi, Commons, and the property continuum - Frerichs, Sabine; James, Rick (Research Handbook on the Sociology of International Law, 2018)
According to the economic analysis of law, an efficient property regime is premised on the universality, the exclusivity, and the transferability of property rights. Ideally then, every (legal) person can enjoy the status of an owner and any (economic) resource can become private property; ownership titles could be bought and sold across national jurisdictions and would ultimately be respected everywhere in the world. Throughout history, property regimes indeed seem to have moved towards this ideal. However, this conception of private property is far less natural than it seems, and not without problems. Instead, the institution of property rights is inherently connected with the development of capitalist society, and it reflects the latter’s underlying tensions. The starting point for a sociological account of property rights is to conceive them as a social relation, or a relation of power, which includes (other) owners and non-owners as well as the state as a ‘third party’. In this chapter, the authors build on the work of Karl Polanyi and John R. Commons to suggest that the property regime of the market society relies both on the reification of property (identifying it with the thing owned) and the commodification of the right of ownership (turning it into a marketable commodity). Looking back, the authors retrace how the concept of property changed with the advent of modern capitalism, and how it evolved in the transition from agricultural to industrial capitalism. Looking into the future, they also address the challenges of today’s informational capitalism, which is characterized by the commodification of knowledge. Based on James’s work, the authors introduce the ‘correlative rights doctrine’ as an alternative to the remnant ‘property rights absolutism’ in the field of intellectual property law, but also beyond. With cross-border conflicts in who owns what having proliferated in the global age, investigations into the relational quality of property rights also matter for international lawyers, who are confronted with new subjects and objects of property, from international investment law to intellectual property law.
Keywords: COMMONS, J.R.; international law; property rights

A moral householding perspective on the sharing economy - Laamanen, Mikko; Wahlen, Stefan; Lorek, Sylvia (Journal of Cleaner Production, 2018)
Abstract In this paper, we scrutinise the sharing economy from a moral householding perspective and evaluate the moral justifications for a sustainable form of the sharing economy. We consider the emergence of normative moral justifications through householding practices that rest on local mobilisation of people in defence of communities and commitments against the adverse impacts of neoliberal market capitalism. Our perspective draws on Karl Polanyi's conceptualisation of householding, that is, autarchic, communistic provision in a closed community. Using timebanking as an example, we illustrate how a moral sharing economy can be mobilised in collective battles against the current neoliberal system of economic crisis. We contribute to the amassing sharing economy literature emphasising a central, yet missing element of the current discourse: householding as practices creating self-sufficiency and autonomy as well as combining both kin and stranger.
Keywords: financial crises; householding; households; market capitalization; mobilisation; moral economy; sharing economy; sustainable development; timebanking

The Truncated Commercialization of Microinsurance and the Limits of Neoliberalism - Bernards, Nick (Development & Change, 2018)
Microinsurance — defined as low‐cost insurance products targeting low‐income populations — exemplifies key themes in contemporary neoliberalism, and has figured prominently in neoliberalism's turn to discourses such as 'risk management' and 'financial inclusion'. The development of commercial markets for microinsurance, however, has in practice been highly variable and often very limited. This article considers the implications of this process of 'truncated commercialization'. It draws on a Polanyian analytical framework that emphasizes the contradictory regulatory dynamics involved in the commodification of labour. The article applies this approach by tracing multiscalar efforts to promote microinsurance, examining the emergence of the concept in the efforts of the International Labour Organization to promote social security for informal workers in the 1980s and 1990s, looking at the adoption of explicitly commercializing imperatives in the work of the International Association of Insurance Supervisors in the 2000s, and, finally, considering a case study of South Africa. The truncated commercialization of microinsurance, it is argued, provides a useful lens through which to see the practical impossibility of neoliberal development strategies.
Keywords: International Association of Insurance Supervisors; International Labour Organisation; commercialization; microinsurance; neoliberalism; social security

What’s Missing - Navickas, Katrina (London Review of Books, 2018)
Capitalism is in crisis, again. Inequality, measured in wages, wealth distribution, employment, ‘affordable’ housing, has become the dominant framework for understanding the economy. Through this lens, people can extrapolate to the macroeconomic from their own individual experiences.
Keywords: MORAL Economists: R.H. Tawney, Karl Polanyi, E.P. Thompson & the Critique of Capitalism, The (Book); POLANYI LEVITT, Kari; POLANYI, Karl, 1886-1964; book review

A political economy of the Poor People’s Campaign: From MLK and Polanyi to Trump - Callebert, Ralph; Soni, Raji Singh (Sikh Formations, 2018)
A stalemate has emerged in mainstream liberal/left responses to Trump. Many commentators prefer to see our predicament in terms of either class-based or identity politics. Vis-à-vis the influence of the Chicago school of economics and its structural adjustment schemes, we crosshatch MLK’s Poor People’s Campaign and Polanyi’s Great Transformation to envision overcoming this stalemate. King’s effort to radicalize the welfare state from below by linking struggles against poverty, racism, and imperialism shares Polanyi’s focus on the economy’s embeddedness in society. We underscore the importance of King’s and Polanyi’s visions for building a leftist coalition that does not divorce social from economic justice.
Keywords: Great Transformation, The (Book); KING, Martin Luther; Poor People's Campaign; TRUMP, Donald; embeddedness

Ritual Matters: Changing Ontologies, Values, and Ecological Conscience Formation - Davy, Barbara Jane; Quilley, Stephen (Journal for the Study of Religion, Nature & Culture, 2018)
Karl Polanyi (1944, 1968) argued that the 'disembedding' of the economy from society entailed a curtailment of social constraints on economic transactions. This disembedding coincided with what Max Weber (1946) called disenchantment, and the erosion of cognitive-experiential reciprocity between humans and nature. Following Lynn White Jr. (1967), many scholars of religion and ecology have argued that losing the sense of divinity immanent in the world caused the modern devaluation of nature. But the loss of ritual practices is key to this. Integrating Roy Rappaport's (1968, 1979, 1999) understanding of the regulative ecological functions of ritual with a processual understanding of ontology following Norbert Elias (1939, 1978, 1989) suggests that reviving ritual gifting practices may be a vehicle for ecological conscience formation and the social-ecological transformation of modern society. Removing the rituals surrounding the giving of gifts removed crucial informal governance structures from pre-modern cultures, resulting in a general collapse of meaning structures in modern market societies, producing a pervasive individualized ontology and what Elias (1991) called 'the society of individuals'. A revival of ritual gifting practices that re-enchant human relations with other than human persons, such as found in what Graham Harvey (2006, 2016) has called 'the new animism', may revive relational ontology and shift modern society toward a more sustainable path by re-embedding the economy in society.
Keywords: POLANYI, Karl, 1886-1964; animism; ecological conscience formation; ecology - religious aspects; environmental behaviour; gift economy; informal governance; new animism; ontology; relational ontology; religion and ecology; ritual; systems theory; systems thinking

Ritual and Economy: From Mutual Embedding to Non-Profit Festivalisation in Provincial Hungary - Hann, Chris (Ritualas ir ekonomika: nuo abipusės nesuprekintos ekonomikos iki nevyriausybinės festivalizacijos provincinėje Vengrijoje., 2018)
'No human beings, at whatever stage of culture, completely eliminate spiritual preoccupations from their economic concerns' (Malinowski 1935: xx). Drawing on the history and theory of economic anthropology from the pioneering investigations of Bronislaw Malinowski to the work of a postdoctoral research team at the Max Planck Institute for Social Anthropology (Halle/S) between 2009 and 2012, this paper* explores the interface between ritual and the economy in socialist and post-socialist Eastern Europe. The ruptures of early socialism gave way to a re-embedding of the economy that was especially dynamic in the sphere of the household. By contrast, postsocialist disembedding is proving harder to modify. (English)
Keywords: (at)kerėjimas; (dis)enchantment; (po-)socializmas; (post-)socialism; Eastern Europe; Karlas Polanyi; MALINOWSKI, Bronislaw, 1884-1942; POLANYI, Karl, 1886-1964; economic anthropology; ekonomikos nesuprekinimas; ekonominė antropologija; embeddedness; ritual; ritualas; social anthropology; socialism

China's Middle East investment policy - Kenderdine, Tristan; Lan, Peiyuan (Eurasian Geography & Economics, 2018)
China's greater Middle East geoeconomic strategy is centered on an external trade and industry policy. This trade and industry policy combines geopolicy and geoeconomic policy to export industrial capacity bases in what amounts to a geoindustrial policy and a parallel trade strategy. Practical coordination is under the umbrella of the central International Capacity Cooperation macro-policy. China's provincial governments are then tasked with offshoring China's industrial capacity to Middle East economies through specialized International Capacity Cooperation funds, which are then coordinated by sectoral industry associations: International Capacity Cooperation Industry Enterprise Alliances. The final industrial policy is then deployed by matching China's provinces and prefectures to external geographies. This amounts to a State Outward Direct Investment Strategy. This paper uses primary sourced Chinese policy documents from central and provincial state administrative agencies to build a historical institutional record. We then employ a Polanyian analysis of the embeddedness of State functions in China's external investment activities and industrial transfers, analyzing China's external trade and industry policy in the Middle East in terms of state–market institutional interrelationality.
Keywords: China; China policy; Middle East; Middle East policy; foreign investments; foreign relations; geoeconomics; geoindustrial policy; geopolicy; institutional economics; investment policy

Rethinking the Double Movement: Expanding the Frontiers of Polanyian Analysis in the Global South - Goodwin, Geoff (Development & Change, 2018)
Over the last two decades a rich and diverse body of literature has emerged which uses the ‘double movement’ to analyse social, political and economic change in the global South. The main aims of this article are to expand the boundaries of this scholarship and improve our understanding of how to use the concept to analyse capitalist development in the region. It seeks to achieve this by explaining and extending the original formulation of the double movement, creating a dialogue between scholars who follow alternative readings of the concept, and proposing a revised formulation which builds on the existing literature while moving in new directions. The article concludes by signposting potentially fruitful areas of Polanyian analysis.
Keywords: capitalism; commodification; developing countries; development studies; double movement; economic reform; liberalism; political change; social change; social movements

Review of The Hungarian Writings by Karl Polanyi - Moussaly, Omer (International Critical Thought, 2018)
In the current times of political crisis, a giant thinker such as Karl Polanyi will return to the forefront of intellectual debate. Many of his important early articles have only been available in Hungarian or in German. With the publication of The Hungarian Writings (2016), edited by Gareth Dale (Senior Lecturer in Politics and International Relations at Brunel University London), a major gap in Polanyi studies has been filled. These essays, published for the first time in English, provide a key to understanding Karl Polanyi’s later works. The range of issues that are reviewed in these writings is astounding. Everything from Marxism to politics, economics and sociology is examined by the extraordinary mind of the author. Events such as the Russian revolution and the significance of Bolshevism are also explored. Lastly, a section of correspondence to such eminent intellectuals as Georg Lukaćs and Istvan Meszaros gives the reader an inside look into the socialist worldview of Karl Polanyi. This book truly shines a new light on many aspects of Polanyi’s critique of capitalism developed in his magnum opus, The Great Transformation (1944). Various aspects of The Hungarian Writings will be explored in depth in this critical review.
Keywords: Bolshevism; Canada; Great Transformation, The (Book); Hungarian Writings, The (Book); Marxism; POLANYI, Karl, 1886-1964; Quebec; Russian Revolution, 1917-1921; economics; nonfiction; socialism

"Race" and the upsurge of antagonistic popular movements in Sweden - Schierup, Carl-Ulrik; Ålund, Aleksandra; Neergaard, Anders (Ethnic & Racial Studies, 2018)
Across a crisis-stricken Europe battles rage for post-neoliberal hegemony, with "race" and "austerity" as central signifiers. One of the places where the frontlines are most pregnant is Sweden; long perceived as a role model for its welfare state, cultural equity and social equality. Sweden is, however, facing social conflicts following in the tracks of a deep transformation in terms of welfare cuts, racialization and growing social polarization, targeting in particular a disadvantaged migrant and post-migrant population. On that background, the paper focuses on the upsurge of mutually antagonistic popular movements - "racist" and "anti-racist". We use Sweden as an exemplary case of Europe's present Polanyian moment, reminiscent of the 1930s. Yet, current upheavals expound, the authors claim, a different configuration of crisis and racism as well as a dissimilar utopia for the imagineering of nation and community.
Keywords: Europe; Sweden; ethnic studies; hostility; immigration opponents; migration; neoliberalism; new right (politics); populism; race; racism; social class; social movements; sociology

Globalization and Business Regulation - Djelic, Marie-Laure; Quack, Sigrid (Annual Review of Sociology, 2018)
In the twenty-first century, global business regulation has come of age. In this article, we review the literature on globalization and business regulation from the angle of transnational governance, a recently evolving interdisciplinary field of research. Despite the multiplicity and plurality of regulatory platforms and products that have emerged over time, we identify common patterns of field structuration and parallel trajectories. We argue that a major trend, both in practice and in scholarly work, is a move away from an idealized convergence around a set of unified global rules; instead, our conceptualizations and our practices of transnational business regulation increasingly demonstrate a concern for the adaptability of transnational rules to resilient and resistant contextual specificities. Another important trend, both in practice and in scholarly fields, is a growing focus on the complex dynamics between rule making on the one hand and rule implementation and monitoring on the other.
Keywords: POLANYI, Karl, 1886-1964; business regulation; globalization; governance; market ideology; neoliberalism; soft law; transnational; value chains

Information Policy and the Spatial Constitution of Digital Geographic Information Markets - Alvarez León, Luis F. (Economic Geography, 2018)
Information policy has become one of the key instruments for the commodification and marketization of goods in contemporary capitalism. However, the spatializing role of this and other legal regimes has not been explored in depth. Among the categories of goods whose production and circulation is shaped by information policy, geographic information is increasingly salient in the digital economy due to the strategic and economic value derived from its integration of location and context. This article explores the role of information policy regimes in spatially bounding, structuring, and regulating digital geographic information markets. This is conducted through a Polanyian economic geographic approach that contextualizes, integrates, and synthesizes two types of geographic information market formations, and focuses on the institutional dimension of information policy regimes. In developing this approach, the article argues that legal regimes (in this case information policy) are capable of spatializing markets by structuring, integrating, and delimiting the actions of states and other actors, such as private corporations and consumers, within particular jurisdictions. The empirical section of the article illustrates this argument by showing how three aspects of information policy—(1) intellectual property, (2) infrastructure, and (3) commercialization—shape specific configurations of digital geographic information markets within the various administrative scales in the European Union, a globally influential jurisdiction for information policy, and where a regional digital market is in the process of construction. The article concludes by arguing that a Polanyian economic geographic approach provides a solid basis with ample versatility to account for the necessary integration of a legal perspective into the analysis of new kinds of goods (such as digital geographic information) and the spatialities of their emerging market configurations.
Keywords: United States; capitalism; digital economy; geographic information; geographic information systems; information markets; information policy; intellectual property; legal frameworks; prediction markets

The economic shift and beyond: Care as a contested terrain in contemporary capitalism - Aulenbacher, Brigitte; Décieux, Fabienne; Riegraf, Birgit (Current Sociology, 2018)
This article argues that we are witnessing a fundamental transformation of capitalism. Under the auspices of an economic shift, social reproduction and constituent care and care work are undergoing a process of reorganization. The first part draws on Karl Polanyi’s analysis of the relation between market and society and on contemporary revisions of his approach. Referring to core arguments from his perspective on the market society it identifies processes of commodification, marketization and quasi-marketization, which we can understand as an economic shift driving the development in the field of care and care work. The second part refers to empirical studies in Austria and Germany and reflects in terms of a Polanyian double movement on how far care and care work – in the case of elder and child care and, more precisely, home care agencies, residential care communities and the social investment state – have become a contested terrain. The third part, the conclusion, points out how tendencies like the economic shift touch care and care work.
Keywords: Giro económico; Virage économique; agence de soins à domicile; agencias de atención a domicilio; atención a los mayores y la infancia; capitalism; care work; communautés de soin; comunidades de atención; corporate reorganizations; doble movimiento; double movement; doublé mouvement; economic shift; elder and child care; home care agencies; inversión social; investissement social; reproducción social; reproduction sociale; residential care communities and social investment; social reproduction; social services; socioeconomics; soin aux personnes âgées et à l’enfance

Political economy and the need for a moral critique of capitalism - Cruddas, Jon (Renewal (0968252X), 2018)
Keywords: Moral Economists: R.H. Tawney, Karl Polanyi, E.P. Thompson & the Critique of Capitalism, The (Book); POLANYI, Karl, 1886-1964; ROGAN, Tim; book review; capitalism; nonfiction

Labour Protest and Industrial Peace: Russian Steelworkers' Encounters with Economic Reforms and Unravelling Social Protections - Evans, Allison D. (Economy and Society, 2018)
The collapse of the Soviet Union brought a series of economic reforms: privatization, increased foreign direct investment and weakened benefits. Correspondingly, some scholars expected trade unions to serve as a major contribution to the development of a democratic civil society that would serve as a Polanyian double movement to these disruptive reforms. However, Russia's steelworkers have stood out as particularly weak and unwilling to strike due to their dependence on their employer for almost all aspects of their livelihoods. But is this lack of large, legally sanctioned and disruptive strikes truly evidence of worker quiescence and weak trade unions? Using an analysis of local newspaper accounts and archival documents to process-trace the interactions of workers, trade unions and management, this paper offers a counter-argument to the generalizations of past studies. Specifically, protests tend to be more frequent and extreme when there is union competition within a company and when foreign owners violate labour laws. Unions tend to engage in non-protest bargaining strategies when companies face bankruptcy or closure under domestic ownership. Because Russia was an early case of the rapid liberalization reforms that have been broadly recommended to developing and post-communist countries, a closer reading of on-the-ground conditions and protest aids in a broader understanding of the variation in backlash to global capitalism.
Keywords: Russia; cement; ceramics; collective bargaining; dispute resolution: strikes, arbitration, and mediation; double movement; glass; industry studies; metals and metal products; population; property rights; socialist systems and transitional economies: factor and product markets; socialist systems and transitional economies: political economy; trade unions: objectives, structure, and effects

The Moral Economists. R.H. Tawney, Karl Polanyi, E.P. Thompson, and the Critique of Capitalism - Gruber, Stephan (Economía (02544415), 2018)
Keywords: book review

Reconstructing Polanyi? - Levien, Michael (Development & Change, 2018)
Most people read Karl Polanyi today because his critique of laissez faire capitalism seems remarkably applicable to our neoliberal times. Although his late work on ancient and ‘archaic’ economies has enjoyed a consistent specialist readership, Polanyi is best known today for his 1944 magnum opus, The Great Transformation (henceforth GT). Covering a large sweep of mostly European history, the GT seeks to show that the attempt to create a ‘self-regulating market’ was a radical and recent departure from all preexisting economies; that this effort to ‘disembed’ the market from society required a great deal of state planning and force; and that the commodification of the ‘fictitious commodities’ land, labour and money was so socially destructive that it generated countermovements that demanded, and in some measure achieved, social protection. Polanyi termed this whole cycle of disembedding and re-embedding the market the ‘double movement’, and tried to show that it was the underlying cause of the great depression, fascism and two world wars. Given the relentless march of commodification in the neoliberal period and the variety of political responses this has generated (from both the left and far right), many people have been drawn to the idea that we are living through another double movement.
Keywords: DALE, Gareth; POLANYI, Karl, 1886-1964; Reconstructing Polanyi: Excavation & Critique (Book); book review; double movement; nonfiction

European Politics and the Neoliberal Paradigm - Sliwinski, Krzysztof (Australian & New Zealand Journal of European Studies, 2018)
This paper looks at the European integration project in its current iteration drawing on Karl Polanyi's assertion that markets are inseparable from the socio-cultural context. In this regard, all attempts to liberalise the economy (not excluding European integration, which is based on the principle of the single market) have practical and indeed tangible political ramifications. The main hypothesis of the paper lies in the recognition of the fact that the neoliberal agenda is one of the defining features of European integration. It is after all, the project of the single market, with its free movement of goods, services, capital, and labour that underpins European Union integrative practice. Secondly, it is the presupposition of this paper, that there is a certain degree of congruence between the economic elites, operating within the neoliberal framework, and the centre-left political elites. The argument here is that the logic of neoliberalism has been fundamentally accepted across the mainstream of the political spectrum. This consequently means that even left-wing parties have had to reposition themselves both ideologically and practically, which brings the conclusion that the market has lost its role as the basic ideological differentiator between the traditional right and left. The axis of political debate has consequently shifted to moral issues such as the relationship between the state and the church, immigration, and gender.
Keywords: EU; European Union; European integration; democracy deficit; international studies; neoliberalism; political ideologies

Capitalism goes care: Elder and child care between market, state, profession, and family and questions of justice and inequality - Aulenbacher, Brigitte; Décieux, Fabienne; Riegraf, Birgit (Equality, Diversity & Inclusion, 2018)
The starting point of the paper is the meteoric rise of care and care work upon the societal and sociological agenda. Referring to Polanyi, the authors argue that this is the manifestation of a new phase of capitalist societalisation (Vergesellschaftung) of social reproduction in the form of an economic shift. The purpose of this paper is to discuss the societal organisation of care and care work and questions of inequality and justice.Design/methodology/approach The first part of the paper illustrates some facets of the economic shift in the field of care and care work. The second part reconstructs the societal organisation of care and care work in the private sector, state, third sector and private households from the mid-twentieth century in the context of questions of inequality and justice. The third part draws on the institutional logics perspective and French pragmatic sociology and the own case studies on home care agencies (HCA), residential care communities (RCC) and early child care (ECC) in Austria and Germany and shows how conflicting demands give rise to new questions of justice. The paper ends with a short conclusion.Findings The paper shows how the commodification and de-commodification of care and care work have changed over time and how the economic shift – illustrated in the case of HCA, RCC and ECC – is accompanied by conflicting demands and questions of justice.Originality/value A Polanyian perspective on the relation between market and society is combined with the neo-institutionalist and pragmatic idea that orientations rooted in the “logics” of the market, the state, the family and the profession influence how conflicting demands in elder and child care are dealt with and how questions of inequality and justice arise.
Keywords: capitalism; care work; caring communities and social investment; community health services; countermovement; decommodification; economic systems; elder and child care; home care agencies; home care services; social justice; social reproduction

A hands-on hands-off approach: governance of managed long-term care services in a context of rapid policy change - Nisbet, Elizabeth (Public Management Review, 2018)
Amidst state-level budgetary pressures and growing elderly populations, many US states have adopted managed care for home-based services funded through the Medicaid program. New York State’s managed care mandate is part of a Medicaid ‘Redesign’ targeting health outcomes, cost control, and administrative efficiency, reflecting features emphasized by both governance and New Public Management frameworks, but neither adequately captures this case. Incorporating a Polanyian perspective can elucidate this market expansion and related reactions and re-regulation. Drawing from interviews with staff of service-providing agencies, this case study reveals outcomes contrary to goals: administrative complexity, containment of care, and unexpected costs.
Keywords: United States; United States federal budget; cost control; governance; health care reform; home care services; long-term care; medicaid; medical care costs; public management

Rethinking Money as an Institution of Capitalism and the Theory of Monetary Circulation: What Can Modern Heterodox Economists/Institutionalists Learn from Karl Polanyi? - Seccareccia, Mario; Correa, Eugenia (Journal of Economic Issues (Taylor & Francis Ltd), 2018)
Modern heterodox theories of money reject the neoclassical conception of money as primarily a medium to facilitate exchange. These heterodox theories of money all have as common starting point an analysis of credit-debt relations in which production is a central feature, with these economies organized along capitalistic design. The Keynesian-Marxian framework describing the process of monetary circulation, traditionally referred to as the theory of the monetary circuit (TMC), perhaps best represents this comprehensive vision. This broad TMC analytical framework is compatible with institutionalist theories of money that also point to the importance of credit-debt relations. The question, however, is whether this more unified heterodox theory of money, which describes sequentially monetary relations under capitalism, can be used to understand pre-capitalistic monetary institutions. By conceptualizing money as a means of payment rather than medium of exchange, Karl Polanyi’s analysis offers social scientists crucial insights to understanding monetary relations in all types of societies in which credit-debt relations have emerged historically.
Keywords: POLANYI, Karl, 1886-1964; credit; credit-debt relations; debt; heterodox economics; monetary circuit; money; money as a means of payment; neoclassical school of economics

In the market for humane rights - Inglis, Fred (Times Higher Education, 2018)
Keywords: Human rights; Moral Economists: R.H. Tawney, Karl Polanyi, E.P. Thompson & the Critique of Capitalism, The (Book); Rogan, Tim; austerity (economics); book review; cultural history; nonfiction

The Double Movement in Polanyi and Hayek: Towards the Continuation of Life - Faria, Filipe Nobre (Ethics, Politics & Society, 2018)
Karl Polanyi’s double movement is a dialectical process characterized by a continuous tension between a movement towards social marketization and a movement towards social protectionism. Notably, Polanyi condemns the former movement while defending the latter. Without using the term “double movement”, F.A Hayek’s theory of social evolution acknowledges the same phenomenon but reaches different normative conclusions. While for Polanyi the marketization of society is a utopia with dystopian consequences, Hayek’s evolutionary explanation of this dialectical process asserts that there is no alternative to a market oriented society. Both authors defend that their favoured movement is the one that truly supports the continuity of life. This article compares the authors’ normative readings of the double movement and concludes that, from an evolutionary perspective, Polanyi’s conclusion possesses a robustness that Hayek’s postulate lacks.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; double movement

Is Capitalism a Threat to Democracy? - Crain, Caleb (2018)
The idea that authoritarianism attracts workers harmed by the free market, a theory that emerged when the Nazis were in power, has been making a comeback.
Keywords: Can Democracy Survive Global Capitalism; KUTTNER, Robert; POLANYI, Karl, 1886-1964; capitalism; democracy; the populist temptation

The Significance of Polanyi's Contribution: An Interpretation of the Neoliberalization and Commodification of Nature - Iannuzzi, Giulia (Janus.Net: e-Journal of International Relations, 2018)
Polanyi's analysis and contributions have been brought back into discussion due to the rapid emergence of market-based instruments designed to tackle environmental degradation. Polanyi is a crucial reference in current debates on globalization and international political economy. This article seeks to explore and discuss how his perspective, and the founding concepts of his work, can help us to interpret the current process of the neoliberalization and commodification of nature.
Keywords: commodification; commodification of nature; environment; globalization; international relations; neoliberalism

Markets in West Africa: Karl Polanyi, or what sort of social formation - Saul, Mahir (Market as Place and Space of Economic Exchange: Perspectives from Archaeology and Anthropology, 2018)
Keywords: West Africa; disembeddedness; economic anthropology; economic history; markets

Polanyi in times of populism: Vision and contradiction in the history of economic ideas - Holmes, Christopher (Routledge, 2018)
The rise of populism across Europe and the US – first in the wake of the 2008 global financial crisis and then in the shape of Donald Trump’s presidential campaign and the Brexit vote in 2016 – are indicative of a seismic shift in the terrain of economic ideas in public discourse. Settled liberal norms concerning ever-increasing international market expansion, and the political integration required to sustain it, have been decisively upset by political forces that, whilst once on the fringes, now dominate economic debate. How might we make sense of this ideological breakdown and what might we hope for next? This book turns to the work of Karl Polanyi for answers, developing the expansive, historicised approach to political economy that Polanyi pioneered. Holmes provides a wide-ranging history of economic ideas read in terms of a series of hopeful theoretical visions of order, in which political, social and ecological contradictions could be transcended in one way or another. Through this, the book demonstrates that the failing utopian visions of pre-2008 economic orthodoxy, which have formed the backdrop to the rise of populism today, are only the latest in a series that stretches across economic thought in Western modernity as a whole. This book will interest students and scholars of IPE, political science, sociology, anthropology, law and history.
Keywords: political science / general; populism

The Great Transformer - Harrison, Roger Gran (American Interest, 2018)
Keywords: Great Transformation, The (Book); economic history; nonfiction; social history

Karl Polanyi's Genealogy of Utopian Liberalism - England, Christopher (Theory & Event, 2018)
Despite its centrality to current debates about globalization and neoliberalism, aspects of Karl Polanyi's The Great Transformation remain poorly understood. This article places Polanyi in conversation with Weber, Nietzsche, and Foucault in order to explicate his genealogy of utopian liberalism. This mode of thought emerged in the late 18[sup th] century as a response to the mass pauperism of the Industrial Revolution in England. It substituted a mechanistic naturalism for the political and ethical concerns of earlier economists. Polanyi shows that the allure of utopian liberalism is sustained because it functions as the public theodicy of a market society.
Keywords: FOUCAULT, Michel, 1926-1984; NIETZSCHE, Friedrich; POLANYI, Karl, 1886-1964; genealogy; globalization; liberalism; neoliberalism; utopian liberalism

Uncertainty, Control, and Karl Polanyi's Protective Response - Zalewski, David A. (Journal of Economic Issues, 2018)
Post-Keynesian institutionalist economists like Wallace Peterson and John Kenneth Galbraith recognized that the impact of uncertainty on economic wellbeing depends in part on the degree of control people have over the sources and consequences of it. Given the inability of government and other large institutions to reduce uncertainty or to provide citizens with the ability to manage it, mediating structures are considered as an alternative means of promoting economic security. The article concludes by describing and evaluating several of these alternatives.
Keywords: Austrian; Stockholm School; criteria for decision-making under risk and uncertainty; current heterodox approaches: historical; evolutionary; general welfare; history of economic thought since 1925: historical; history of economic thought: individuals; institutional; well-being

The Moral Economists: R. H. Tawney, Karl Polanyi, E. P. Thompson, and the Critique of Capitalism - Crook, Paul (Australian Journal of Politics & History, 2018)
The Moral Economists: R. H. Tawney, Karl Polanyi, E. P. Thompson, and the Critique of Capitalism. By Tim Rogan (Princeton and Oxford, Princeton University Press, 2017), pp.263 + viii. AU$48.82 (hb). Available in Australia through Footprint Books.
Keywords: MORAL Economists: R.H. Tawney, Karl Polanyi, E.P. Thompson & the Critique of Capitalism, The (Book); POLANYI, Karl, 1886-1964 - political & social views; ROGAN, Tim; TAWNEY, R. H. (Richard Henry), 1880-1962; THOMPSON, E. P. (Edward Palmer), 1924-1993; book review; nonfiction; political attitudes

Beyond Double Movement and Re-regulation: Polanyi, the Organized Denial of Money Politics, and the Promise of Democratization - Feinig, Jakob (Sociological Theory, 2018)
Although Karl Polanyi is best known for his theorization of market regulation and the double movement, democratizing the economic was one of his core concerns. He believed societies need to bring labor, land, and money under collective oversight to displace the logic of market fundamentalism with the logic of human needs. In this article, the author draws on Polanyi’s vocabulary to shed light on the denial of money politics and the possibility of democratization. The author illustrates these dynamics through an analysis of long-term dynamics of (de)politicization in British colonial America and the United States through the 1930s. The author developed this approach hoping that it can contribute to nudging public debates beyond regulation and monetary policy techniques and toward popular involvement and knowledge.
Keywords: Polanyi; democratization; depoliticization; double movement; gold standard; money; social theory; sociology

Situated responses to the post‐political city: An introduction - Richter, Anna; Fitzpatrick, Susan (Area, 2018)
It seems with the ever more complex instituting of aggressive neoliberal renewal policies comes an intensified effort to use the language of consensus and civic unity. The post‐political debate frames this discussion, and it is from this perspective that we propose a fuller consideration of urban renewal policy, and how these forces are embedded within the narrowing of what has been called the “properly political”. In bringing together accounts of the dynamic political life of communities and groups of interest who are confronting urban renewal policy in Glasgow, we make a case for recognising an intensification of political articulation, position‐taking and action. This recognition comes in response to the argument that we are currently experiencing a post‐political consensus and that democracy has been annulled in the process. We see evidence of a Polanyian “double movement” in which the construction of consensual publics is such a marked characteristic across different accounts, and how this appears to have opened up new critical spaces of debate and action within the various communities of interest. We therefore openly question the post‐political as a condition, or a process, which seemingly unfolds unimpeded. We fear that “post‐political” runs the risk of becoming a citational practice, that through repetition of the term, a narrowing of political articulation and action within the debate starts to occur. Our case studies aim to highlight the blind spots of the post‐political debate by focusing on the actually existing spaces of political articulation and position‐taking apparent in Glasgow.
Keywords: Glasgow; articulation (speech); consensus (social sciences); debates & debating; political; urban policy; urban renewal

A Theoretical Note on Commodification of Labour Power in China and the Global Putting-Out System - Westra, Richard (Journal of Contemporary Asia, 2018)
This article captures China's role in global manufacturing through the prism of conceptualisation of the commodification of labour power in Marxist theory. It argues that modalities of China's labour force co-optation in assembly and lower value added production for export of consumer goods to advanced economies carries more of a family resemblance with putting-out systems of the pre- capitalist era than with the commodification of labour power sensu stricto marking the capitalist era from the mid-nineteenth century.
Keywords: China; MARX, Karl, 1818-1883; POLANYI, Karl, 1886-1964; capitalism; commodification; commodification of labour power; consumer goods; global value chains; globalization; international trade; labour supply; manufacturing industries; putting-out system; value chains

Discursive Synergies for a ‘Great Transformation’ Towards Sustainability: Pragmatic Contributions to a Necessary Dialogue Between Human Development, Degrowth, and Buen Vivir - Beling, Adrián E.; Vanhulst, Julien; Demaria, Federico; Rabi, Violeta; Carballo, Ana E.; Pelenc, Jérôme (Ecological Economics, 2018)
There is a growing awareness that a whole-societal “Great Transformation” of Polanyian scale is needed to bring global developmental trajectories in line with ecological imperatives. The mainstream Sustainable Development discourse, however, insists in upholding the myth of compatibility of current growth-based trajectories with biophysical planetary boundaries. This article explores potentially fertile complementarities among trendy discourses challenging conventional notions of (un)sustainable development – Human Development, Degrowth, and Buen Vivir – and outlines pathways for their realization. Human Development presents relative transformative strengths in political terms, while Degrowth holds keys to unlocking unsustainable material-structural entrenchments of contemporary socio-economic arrangements, and Buen Vivir offers a space of cultural alterity and critique of the Euro-Atlantic cultural constellation. The weaknesses or blind spots (‘Achilles heels’) of each discourse can be compensated through the strengths of the other ones, creating a dialogical virtuous circle that would open pathways towards a global new “Great Transformation”. As one of the main existing platforms for pluralist and strong-sustainability discussions, Ecological Economics is in a privileged position to deliberately foster such strategic discursive dialogue. A pathway towards such dialogue is illuminated through a model identifying and articulating key discursive docking points.
Keywords: biophysics; degrowth; ecosystem services; environemntal economics; post-development; pragmatics; socio-ecological transition; strategic dialogue; sustainable development; transformation discourses

In Search of Substantive Economics: Comparing Today's Two Major Socio-metabolic Approaches to the Economy – MEFA and MuSIASEM - Gerber, Julien-François; Scheidel, Arnim (Ecological Economics, 2018)
Ecological economics is largely about the ‘substantive’ (in ‘kind’) study of the economy, as opposed to a purely ‘formal’ economic analysis (in ‘money’). Following Kapp, Polanyi and others, this article argues that ‘substantive economics’ is interested in the biophysical and politico-institutional structure of the economy rather than in correct prices within a particular axiomatic conformity, as in ‘formal economics’. After outlining the history of the substantive vs. formal dichotomy, we point out that socio-metabolic analyses are ecological economics' most significant contribution towards substantive economics. The core of this article then compares what could be today's two best candidates for offering a distinctive foundation to ecological economics as substantive economics: Material and Energy Flows Analyses (MEFA) and Multi-Scale Integrated Analyses of Societal and Ecosystem Metabolism (MuSIASEM). While MEFA is more easily comparative and historical, MuSIASEM is more integrative and comprehensive. Yet we also argue that socio-metabolic analyses represent one of the three pillars of substantive economics and that both MEFA and MuSIASEM are still weak in integrating the politico-institutional structure (second pillar) and a theory of needs (third pillar). If such an integration was done, ecological economics would be in a position to offer a full-fledge, alternative ‘substantive economic theory’.
Keywords: MEFA; MuSIASEM; biophysics; comparative studies; ecological economics; economic impact; environmental economics; social metabolism; substantive economics

Reconstructing Karl Polanyi: Excavation and Critique - Neelakandan, Sanil M. (Capital & Class, 2018)
Keywords: DALE, Gareth; POLANYI, Karl, 1886-1964; Reconstructing Karl Polanyi: Excavation & Critique (Book); economists; nonfiction

Costly Fix: Power, Politics, and Nature in the Tar Sands - Urquhart, Ian Thomas (University of Toronto Press, 2018)
Costly Fix examines the post-1995 Alberta tar sands boom, detailing how the state inflated the profitability of the tar sands and turned a blind eye to environmental issues. It considers the position of First Nations, the character and strength of environmental critiques, and the difficulties that environmental groups and First Nations have had in establishing a countermovement to market fundamentalism. The final chapter discusses how Alberta's new NDP government, in its first couple of years, has addressed the legacies they have inherited from the previous Progressive Conservative government on climate change, royalties, and the blight of tailings ponds in the boreal forest. Throughout the book, Urquhart demonstrates that too many actors have done too little to prevent Alberta's boreal forest from becoming a landscape sacrificed for unsustainable economic growth.
Keywords: Alberta; Canada; First Nations; double movement; environmentalism; tar sands

Latin American Structuralism and Current Financialization - Déniz, José; Marshall, Wesley C. (International Journal of Political Economy, 2018)
In this article, we attempt to update the understanding of the external constraint in Latin America by examining the recent history of the region through the analytical framework of Karl Polanyi in The Great Transformation. As we argue, the greatest force behind today’s external restriction is the financial sector, much as it was a century ago. To reinforce this hypothesis, we provide the reader with relatively new historical material and with arguments made by scholars from diverse backgrounds. Taking into consideration the political and economic structures of Latin America, we argue that the international connections between the elite of the center and the periphery remain the key aspect in understanding today’s complex reality.
Keywords: Great Transformation, The (Book); Latin America; POLANYI, Karl, 1886-1964; external restriction; financialization; structuralism

The agrifood question and rural development dynamics in Brazil and China: towards a protective ‘countermovement’ - Escher, Fabiano; Schneider, Sergio; Ye, Jingzhong (Globalizations, 2018)
This paper explores some features of the development paths taken by Brazil and China (two member countries of the BRICS grouping) in the current context of the crisis of neoliberal globalization and transformation of the political and economic world order. The authors use Polanyi’s ‘double movement’ thesis to argue that newly emerging rural development (RD) dynamics in China and Brazil are part of a protective ‘countermovement’, driven by actors and institutions responding to the contradictions of the concentration and internationalization of agrifood systems. However, thedirectionand scope of these countermovements are still open; their transformative potential should be viewed in Gramsci’s terms as a struggle for hegemony the outcome of which depends on the concrete ‘balance of social forces’. First, the paper characterizes the impacts of China’s rise on Brazil’s development, which subsequently found its economy under threat of reprimarization and deindustrialization. The paper then sketches some stylized facts of production and consumption within the Brazil–China soy–meat complex, a key element of the current global food regime, with a focus on corporate control of the soy–meat value chain, and its negative consequences. Finally, the paper identifies the key roles that actors and institutions linked to peasants and family farmers are playing in the RD dynamics of each country. Although China and Brazil represent two very different realities, the comparison shows that critical rural and agrifood issues are indeed moving onto the centre stage of the contemporary ‘double movement’.
Keywords: Brazil; Brazil–China soy–meat complex; China; deindustrialization; double movement; farming practices; food industry; globalization; production–consumption relations; rural development; rural policies

The Double Movement of the Landlord Class in Prewar Japan - Cohen, Mark (Journal of Japanese Studies, 2018)
The role of the landlord class in Japan's prewar economic and political development has been widely debated. Moving beyond conflicting arguments of landlords as semifeudal exploiters or as the linchpins of rural market development, more recent research has emphasized the nonmarket institutions, often inherited from the Tokugawa era, in which the contractual relations between landlords and tenants were embedded. However, this research has overemphasized the continuity of the rural economy. Rather than a smooth development, the historical trajectory of rural economic growth followed the "double movement" of capitalist development identified by the historian and economic anthropologist Karl Polanyi.
Keywords: Japan; Tokugawa Period, Japan, 1600-1868; capitalism; double movement; history; landlord-tenant relations

Karl Polanyi vs Friedrich von Hayek: The Socialist Calculation Debate and Beyond - Dale, Gareth (Hayek: A Collaborative Biography: Part XIV: Liberalism in the Classical Tradition: Orwell, Popper, Humboldt and Polanyi, 2018)
It is well known that Friedrich von Hayek’s The Road to Serfdom and Karl Polanyi’s The Great Transformation were written contemporaneously (between 1940 and 1943), that their authors propounded antithetical political ideologies (right-wing liberalism and left social democracy respectively), and that the two books revolve around a similar problematique: the causes of the collapse of liberal order in the interwar era. This chapter undertakes a detailed comparison of Hayek and Polanyi’s Weltanschauung (including ethics, economic analysis, and political perspectives). It reveals a chequered picture, in which diametrically opposed political views articulate with points of striking agreement in economic analysis. This helps to explain the manner in which certain Polanyian theses, notably on the ‘constructed’ market order and the ‘spontaneous’ social-movement response, appear to mirror those of Hayek.
Keywords: Great Transformation, The (Book); HAYEK, Friedrich A. von (Friedrich August), 1899-1992; Polanyi; constructed market order; history of economic thought; liberalism; methodology; socialist calculation debate

Reconstructing Globalization in an Illiberal Era - DeMartino, George F. (Ethics & International Affairs, 2018)
In their new indictments of global neoliberalism and the economic profession's culpability in its harms, Dani Rodrik and Joseph Stiglitz press the case for reconstructed globalization that generates benefits for all and not just for corporate and financial elites. Both books are deeply consistent with the insights of Karl Polanyi, who had identified the inherent contradictions of the project to create what he called a self-regulating economy. Like Polanyi, Rodrik and Stiglitz are attentive to the inadequacies of neoliberalism, and both emphasize the capture of the state and international economic policy by elites, who have turned their backs on those left behind. While Stiglitz emphasizes that the profession knows how to fix the problem by applying modern Keynesian insights, Rodrik emphasizes the inherent epistemic limitations facing economists. Indeed, his arguments about development policy reflect the insights of Friedrich Hayek into the limits of economic expertise.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; RODRIK, Dani; STIGLITZ, Joseph; globalization; international relations; nationalism; neoliberalism; policy autonomy; trade; uncertainty

Capabilities Accumulation and Development: What History Tells the Theory - Dosi, Giovanni; Yu, Xiaodan (2018)
In this contribution we offer a broad overview of the technological, institutional and policy dynamics associated with the great transformation--borrowing Karl Polanyi (1944) expression--leading from traditional, mostly rural, economies to economies driven by industrial activities (and nowadays also advanced services), able to systematically learn how to implement and eventually how to generate new ways of producing and new products under conditions of dynamic increasing returns. Such a 'great transformation' entails a major process of accumulation of knowledge and capabilities, both at the levels of individuals and organizations. Certainly, part of such capabilities builds on education and formally acquired skills (what in the economists' jargon often goes under the heading of 'human capital'). However, at least equally important, capabilities have to do with the problem-solving knowledge embodied in organizations--concerning e.g. production technologies, the technical and social division of labor, labor relations as well as 'dynamic capabilities' of search and learning. In turn, the rates and directions of knowledge accumulation during the catch-up process and the ensuing effects upon the patterns of production and trade are shaped by the economic and institutional framework in which such processes are embedded.
Keywords: Great Transformation, The (Book); capability accumulation; catching-up; development; innovation

Summoning Hunger: Polanyi, Piers Plowman, and the Labor Market - Epstein, Robert (Money, Commerce, and Economics in Late Medieval English Literature, 2018)
The “plowing of the half-acre” episode in Langland’s Piers Plowman includes a chilling passage in which Piers summons Hunger to force able but unwilling laborers to work the land. This chapter approaches the episode by way of the economic history of Karl Polanyi, whose critiques of free-market ideology are receiving renewed attention in the context of globalization and the international economic crisis. One of Polanyi’s key points is that the threat of starvation is a prerequisite to the institution of a true labor market—meaning that first the networks of collective support that peasants rely on for survival need to be undermined. The summoning of Hunger shows that Langland is actually more free market in his ideology than are the landowning supporters of the labor statutes.
Keywords: LANGLAND, William; Piers Plowman (book); economic history; globalization; hunger; threat of starvation

Polanyi's Economic Embeddedness, Countermovement, and Republican Political Economy - Escandell, Bru Laín (Ethics, Politics & Society, 2018)
The aim of this article is to contend that Karl Polanyi's work bears significant coincidences with the republican tradition of thought. The first of them is one of a methodological or epistemological kind, and it consists of the use of a very
Keywords: countermovement; embeddedness; political economy; political economy and history; political philosophy; republicanism

Capitalism: A Conversation in Critical Theory - Fraser, Nancy; Jaeggi, Rahel (John Wiley & Sons, 2018)
In this important new book, Nancy Fraser and Rahel Jaeggi take a fresh look at the big questions surrounding the peculiar social form known as “capitalism,” upending many of our commonly held assumptions about what capitalism is and how to subject it to critique. They show how, throughout its history, various regimes of capitalism have relied on a series of institutional separations between economy and polity, production and social reproduction, and human and non-human nature, periodically readjusting the boundaries between these domains in response to crises and upheavals. They consider how these “boundary struggles” offer a key to understanding capitalism’s contradictions and the multiple forms of conflict to which it gives rise. What emerges is a renewed crisis critique of capitalism which puts our present conjuncture into broader perspective, along with sharp diagnoses of the recent resurgence of right-wing populism and what would be required of a viable Left alternative. This major new book by two leading critical theorists will be of great interest to anyone concerned with the nature and future of capitalism and with the key questions of progressive politics today.
Keywords: boundary struggle; capitalism; political philosophy; triple movement

Reconfiguring the social and solidarity economy in a Danish/Nordic welfare context - Hulgård, Lars; Andersen, Linda Lundgaard (3rd EMES-Polanyi International Seminar. Welfare societies in transition. Polanyi revisited through the lens of welfare state, social democracy and solidarity economy, 2018)
When looking at definitions and understandings of the social and solidarity economy, one issue stands out as particularly significant. The issue of how it links to organizational (micro and meso level dimensions) and societal specificities. Whereas social enterprise also in the EMES ideal typical version (Borzaga & Defourny, 2001) is only indirectly linked to a Polanyian framework (Gardin, 2006), the notion of solidarity economy can hardly be understood at an elaborate level without reference to the Polanyian framework of plurality. Accordingly, in this paper we will first highlight the difference between adopting a social economy and a solidarity economy approach to social enterprise and social entrepreneurship. Within the framework of a social economy perspective, social enterprise is first defined through a set of organizational criteria leaving the relation to the broader and deeper issues of economy and democracy open. As a contrast to this, solidar-ity economy links the organizational dimension of a particular social enterprise to the broader political and economic framework of the particular society (Laville, 2010: 230 ff.). Secondly, we will present and discuss two specific social enterprises that both re-flects the diversity of social enterprise and social entrepreneurial initiatives in a Danish welfare context and provide important insights for developing theories on solidarity economy. The two initiatives differ in shape, space/geography and organizational struc-ture but are important examples of pluralism in a Danish welfare context (Andersen, 2015). Roskilde Festival and Skovgård Hotel share a number of features that place them as interesting agents of solidarity economy. They both display a differentiated activity portfolio of business; public and civil character and they display a differentiated profile of reciprocity, redistribution and democracy that place them as influential in local, regional and national/international contexts. Finally, in the concluding section we discuss how an analysis based upon solidari-ty economy differ from one based solely upon a social economy perspective, and second-ly some future perspectives for the continued evolution of the Danish/Scandinavian wel-fare model.
Keywords: Denmark; plurality; social economy; social enterprise; social entrepreneurship; solidarity economy

The social aftermath of economic disaster: Karl Polanyi, counter-movements in action, and the Greek crisis - Kentikelenis, Alexander E. (Socio-Economic Review, 2018)
The economic crisis in Greece resulted in high unemployment and the dismantlement of social protection policies. How does society respond to the collapse of both welfare-state and market mechanisms? I examine these issues through the study of one working class community in Athens over 2012-13. Since the onset of the crisis, my informants experienced a simultaneous drop in living standards, loss of social status, and debasement of their symbolic construction of reality. To respond to these pressures, they relied on a combination of material survival strategies, the reconfiguration of social resources, and the reconstruction of cultural imaginaries. To explain these findings, the article draws on Karl Polanyi's analysis of countermovements to marketization and commodification. I argue in favour of augmenting the definition of countermovements to capture local-level responses, emphasising cultural aspects of social protection, and tracing the micro-foundations of countermovements that are nonetheless shaped by the macro-institutional context shaping action. This reading of Polanyi's work seeks to integrate many moving--and potentially contradictory--parts into a holistic analysis of societal responses to rapid and radical socioeconomic change.
Keywords: Greece; capitalist systems: political economy; countermovement; economic crisis (2008); financial crises; history of economic thought: individuals; national government expenditures and welfare programs

How the market abandoned morality - Mason, Paul (New Statesman, 2018)
Like the lifelong sinner who makes a deathbed conversion, it was always likely that supporters of neoliberal globalisation would rediscover ethics towards the end. Having devastated communities through indifference, and coercively imposed commercial priorities on to family life, the political “centre” now has to deal with anger, distrust and rejection on an unmanageable scale. In The Future of Capitalism, Paul Collier, a former chief economist at the World Bank, now professor at the Oxford Blavatnik School of Government, attacks the twin ethical systems that have dominated policymaking in the free-market era: utilitarianism and the theories of social justice associated with the political philosopher John Rawls. In their place he outlines a project for the renewal of centrist politics based on communitarian ethics. The project, which he labels “hard centrism”, is backed by an appeal to patriotism and with a mea culpa from the economics profession. We over-egged the benefits of globalisation, trade, migration and light-touch regulation, and the result is an outbreak of fascism and xenophobia from Charlottesville to Katowice. If it were coherent, Collier’s solution might place him as the latest in a line of “moral economists”, broadly aligned with the centre left and stretching from RH Tawney in the 1920s, via Karl Polanyi to Edward Thompson, whose evolution is explored in Tim Rogan’s book The Moral Economists. Unfortunately, Collier’s solutions are not coherent, and about as likely to defuse populist anger as a Goldman Sachs away-day. Collier correctly identifies the symptoms that are driving political radicalisation: the massive inequalities generated by free-market economics; the spatial divide between ex-industrial towns, with their older and less educated workforce, and the buzzing, young cosmopolitan cities; plus the absence of empathy among those who’ve gained under neoliberalism for those who’ve lost out. But for Collier, the root cause of these malfunctions is not the structure of the neoliberal economy itself, nor the rapaciousness of a small financial elite. It is, instead, the rise of a new skilled and salaried middle class who can capture the economic and social gains generated by highly productive and asset-rich city economies. “The newly successful,” writes Collier, “are neither capitalists nor ordinary workers; they are the well educated with new skills. They have forged themselves into a new class, meeting at university and developing a new shared identity in which esteem comes from skill.” This group, says Collier, has not only captured policymaking but, to rub salt in the wound, developed an ideology whereby they – because of their mixed ethnicity and liberal sexuality – can portray themselves as victims in greater need of sympathy than the working poor, and at the same time justify their own lack of ethical belief. Collier’s identification of the urban salariat as a “new class” is not simply a metaphor. He classifies the typical behaviours of young, urban, educated people as economic “rent-seeking”, which, in traditional economics, refers to activities designed to increase your own wealth without increasing the wealth of society. It can range from property speculation to trying to rig government regulations to favour your firm. Collier, however, sees the lifestyle of educated urban people as the same kind of thing. Ducking and diving to get a decent job, investing in private tuition to improve your skills, “delaying marriage or delaying children” – each of these is portrayed as a form of exploitative behaviour, detrimental to the small-town poor, which must be discouraged by taxation and regulation. Just as Keynes wanted “euthanasia of the rentier”, Professor Collier wants fewer lawyers, fewer actors, fewer migrants and fewer people avoiding marriage and family life. If you are wondering what kind of politics emerges from all this, you will not be surprised to learn it is a form of social-democratic conservatism, severely critical of Bernie Sanders, Jean-Luc Mélenchon and Jeremy Corbyn – whose followers are written off as “youthful idiots”. Collier wants to save neoliberalism through a distributional attack on the urban salariat and a repudiation of its morality. So, although he wants to discourage high property values in cities, he is against rent control – which is too Marxist – and against a sudden programme of housebuilding, because it risks tanking house prices. To protect the political system from an enraged radical populace, Collier advocates depriving members of political parties from selecting who leads them – better that only elected representatives should have a say. There is a logic to the nostalgia. Since the most successful and inclusive form of capitalism in our lifetime was the communitarian statism of the 1950s and 1960s, to recreate it Collier argues we have to discourage the morality and lifestyle of educated, mercurial and seemingly amoral young people, limit the migration that is annoying low-skilled people, and promote the “ethical family” and patriotism as the roots of shared identity. But it is a doomed project. First, because it frames the task of renewing capitalism in opposition to the social values of the rising generation. Second, because, unlike the project of the radical left, which seeks to free the young generation from debt peonage and stagnating wages, Collier wants explicitly to penalise them until their behaviour falls into line with the communitarian project. Third, because it avoids the root of the problem: a system mired in financial rent-seeking by super-rich elites and geared to boom, bust and speculation, with an ever-greater fiscal hangover limiting public investment and growth. To these problems, which are the source of radicalisation to the left, Collier’s solutions are timid. Yet the central call of Collier’s book – for a return to ethics in policymaking – is welcome. For as Tim Rogan points out in The Moral Economists, it is remarkable how unmoral the left’s critique of capitalism has become. Across the developed world the dysfunctions of free-market economics are seen as negative material outcomes: rising inequality, low growth and poor social mobility. While the left’s emphasis on material inequality seems unremarkable, says Rogan, “in historical perspective it is extraordinary… An alternative tradition focused less on material outcomes than on moral or spiritual consequences has fallen into disuse.” Surveying the work of Tawney, Polanyi and Thompson, Rogan shows how the 20th-century moral critique of capitalism was rooted in humanism, in part derived from the Judeo-Christian religions, and in part from their last prophet – the early Marx. The attack on humanism after the 1960s, first by structuralist Marxism and then by postmodernism, stripped the left’s moral critique of capitalism of its confidence. For the followers of Louis Althusser, history was a “process without a subject”. The downsides of capitalism had to be calculated functionally – in terms of the rising technology clashing with old forms of social organisation – and not against the moral claim of working-class people to a fully human life, which was seen as a hangover from Christian socialism. Each of the theorists Rogan surveys studied the transition from late feudalism to early capitalism, observing the death of a pre-capitalist moral universe as industrialisation and commerce introduced utilitarian ethics to the masses. Each also observed among the 20th-century working class a surviving moral critique of capitalism and an alternative moral practice: Tawney found it in the everyday solidarity of his contemporaries in the Potteries; Thompson in the literate and cultured lives of the 19th-century pioneers of labour he studied in The Making of the English Working Class (1963). Each, in turn, tried to ground this plebeian moral alternative in something theoretical: for Tawney it was Christian socialism, for Polanyi a rereading of Adam Smith and for Thompson the early Marx. Ultimately, Rogan shows, they were all unsuccessful, leaving the ethical framework for 21st-century capitalism open to the forces Collier derides: utilitarianism and Rawlsian justice theory. Which begs the question: what might be the moral basis for a critique of neoliberal capitalism, should anybody beyond a few nostalgics be in the market for it? If we are to judge the Gestapo-like tactics of the Department for Work and Pensions, the actions of Brett Kavanaugh, or Duterte’s death squads in the Philippines as merely dysfunctional to the operation of the free market and the rule of law, then we don’t need a moral philosophy. The airport bookshelves are groaning with blockbusters insisting humans are “already algorithms”, under the complete control of our DNA and our smart devices, and thus absolved by neuroscience from moral responsibilities founded on human values. For Collier, the biggest mea culpa neoliberalism must deliver is over the destruction of community, without which reciprocal obligations cannot give rise to shared values. But having rejected utilitarianism and social justice, Collier never suggests what the source of a new shared value system might be, other than a spontaneous mass return to the thought-patterns and behaviours of his home town, Sheffield, in the 1960s. People shaped by 30 years of compliance with neoliberalism, for whom freedom has come to mean the ability to choose between latte and cappuccino, cannot return to the value systems of their grandparents. A new moral critique of capitalism would have to be based on a shared concept of the human rights accruing to an adult with a smartphone, a credit card and a Tinder account. The networked generation, written off as amoralists and rent-seekers by Collier, are in fact engaged intensely in questions of practical morality, above all via the agony columns and private social networks of advice. Is it right to “ghost” somebody you slept with but didn’t like? Can polyamory work without someone getting exploited? Can you snort cocaine without becoming complicit in the destruction of rainforests? Though these questions sound facile to the older generation, they should be read as evidence that the young generation is searching for an alternative morality, albeit in a largely godless world. Among the networked social movements of the past ten years, from the British student revolt in late 2010, via Greece and Turkey, through to #MeToo and Corbynism, I’ve found an implicit moral critique of capitalism amounting to this: it dulls human potential, requires absurd levels of performative behaviour, and makes you unhappy. Though that is not the same critique as the one Tawney found in Staffordshire, or Polanyi in 1920s Red Vienna, it is an implicit moral system none the less, and rooted the same desire to live a fully human life. Looked at this way, the networked individuality that characterises the new demos of the 21st century is something more than selfish amoralism. This group, too, can generate oppositional movements, ideologies and projects. It, too, can be communitarian: witness any music festival, or rave, or just a beach such as Brighton or Bondi on a really busy summer’s day. If so, the 21st century will not play out as a battle between the emotionalism of the extremes versus the pragmatism of the centre. It will be a struggle over which moral critique of neoliberalism wins. In that struggle, a truly “hard centre” would make a choice: to ally with the left, with the radical movements inspired by Corbyn, Mélenchon and Sanders, against the fascists, misogynists and xenophobes, wallowing in nostalgia. It’s a choice modern centrism seems determined to avoid making. Paul Mason’s “Clear Bright Future: A Radical Defence of the Human Being” will be published next year by Allen Lane The Future of Capitalism: Facing the New Anxieties Paul Collier Allen Lane, 256pp, £20 The Moral Economists: RH Tawney, Karl Polanyi, EP Thompson, and the Critique of Capitalism Tim Rogan Princeton University Press, 280pp, £30
Keywords: MORAL Economists: R.H. Tawney, Karl Polanyi, E.P. Thompson & the Critique of Capitalism, The (Book); book review

Karl Polanyi and the formation of this generation's new Left - Sandbrook, Richard (IPPR Progressive Review, 2018)
The article discusses whether the visionary thinking of economic historian Karl Polanyi provide a feasible fix in the 21st Century for forces of populism and neoliberalism. Topics include Polanyi's work is stated to offer three potential contributions to the formation of this generation's new Left which include analysis of fascism, post-Vienna approach to socialism.
Keywords: POLANYI, Karl, 1886-1964; fascism; neoliberalism; populism; socialism